The Adam Smith review (London)
1 online resource.
Keywords: Adam Smith's contribution to economics is well recognised,yet scholars have recently been exploring anew the multidisciplinary nature of his works. The Adam Smith Review is a rigorously refereed annual review that provides a unique forum for interdisciplinary debate on all aspects of Adam Smith's works, his place in history, and the significance of his writings to the modern world. It is aimed at facilitatingdebate amongscholars working across the humanities and social sciences, thus emulating the reach of the Enlightenment world which Smith helped to shape. This twelfth volume brings together leading scholars from across several disciplines andcontributes to two particular themes. First, there is a focus on Adam Smith's moral and political philosophy, exploring how Smith's approach finds expression in both abstract philosophy and practical judgment. Second, there is a focus on epistemology, economics, and law, with innovative interpretations of Smithian theories.